Animals and sacred bodies in early medieval Ireland religion and urbanism at Clonmacnoise - Soderberg, John (Professor of archaeology) (Lexington Books, 2022)
"Clonmacnoise was among the busiest, most economically complex, and intensely sacred places in early medieval Ireland. In Animals and Sacred Bodies in Early Medieval Ireland: Religion and Urbanism at Clonmacnoise, John Soderberg argues that animals are the key to understanding Clonmacnoise's development as a thriving settlement and a sacred space"--